GP203 Paediatric nosocomial and health care worker transmission during measles outbreak, dublin 2018. (June 2019) - Marron, Louise; McDermott, Ruth; Conway, Robert; Ennis, Orla; Bruton, Orla; Ward, Mary; Murray, Helena
Abstract : Background: Despite achieving measles elimination status in 2018, Ireland remains vulnerable to measles outbreaks following imported cases. Overall uptake of two doses of MMR vaccine is suboptimal. Pockets of under immunised populations vulnerable to measles reflect anti-vaccination sentiment as well as difficulty accessing services among deprived and marginalised communities. A measles outbreak occurred in North Dublin in July 2018 with important public health and health service implications including nosocomial paediatric transmission and health care worker transmission in an adult hospital. Methods: A delayed diagnosis of measles in a child recently returned from Europe was the index case in a measles outbreak which spread in healthcare settings and within an inner city area. Epidemiological investigation determined demographic characteristics, vaccination status and transmission pathways of cases. Management of the outbreak included isolation, contact tracing, exclusions, and post exposure prophylaxis with MMR vaccine and immunoglobulin for appropriate contacts. Public health alerted general practitioners, adult and paediatric emergency departments, microbiologists and occupational health physicians to the outbreak. Social inclusion and community health services supported targeted control measures for vulnerable exposed communities. An extensive awareness campaign was undertaken involving print, radio, TV and geo-targeted social media messaging. Results: There were 17 confirmed cases. Eight (47.1%) occurred in adults and nine (52.9%) in children. Four (23.5%) were under 12 months old. Two (11.8%) were health care workers with complete MMR vaccination and reported relatively mild illness. Thirteen cases (76.5%) attended emergency departments and four (23.5%) required hospitalisation. Eleven (64.7%) were unvaccinated, including four infants (23.5%). The primary case was travel acquired; household transmission occurred in seven cases (41.2%); nosocomial transmission occurred in six cases (35.3%) and in three cases (17.6%) the route of transmission was unknown. Over 400 children were exposed in emergency healthcare settings resulting in three attributable cases. Measles transmission also occurred between paediatric in-patients. Eight infants received human normal immunoglobulin following exposure. Implications: Following an imported case of measles, transmission occurred from multiple healthcare exposures and within under-vaccinated households in socially deprived areas. This outbreak highlighted: delayed recognition of measles facilitating nosocomial transmission; unusual clinical presentations among adults; vulnerable unvaccinated populations including children under 12 months and transmission to vaccinated healthcare workers which did not result in onward transmission. In addition recent changes in the national guidelines for providing post exposure prophylaxis with immunoglobulin to young infants presented logistical challenges when delivered in the hospital setting.